Efek Teknologi Informasi dan Work Life Balance Terhadap Kinerja Karyawan Pada New Normal : Efek Teknologi Informasi dan Work Life Balance Terhadap Kinerja Karyawan Pada New Normal - Lukmana Putra, Indra (Apik Cahaya Ilmu, 2024)
The development of information technology has developed and influenced employee performance behavior in a business entity, especially in the new normal era where terms such as work life balance have emerged. The main aim of the research is to analyze the influence of information technology and work-life balance on employee performance. Both have the effect of supporting employee performance. Information technology and work-life balance as variables to assess the influence of employee performance. This research uses a quantitative approach with the type of explanatory research. The form of research observation is in the form of surveys and questionnaires. The research results show that information technology and work-life balance have a significant influence on employee performance in multinational business entities in the New Normal era. So it is known that information technology and Work Life Balance variables have a positive effect on employee performance in the New Normal era. Keywords: Information Technology, Work Life Balance, Employee Performance